Balancing livestock environment and human needs: An international perspective - Li Pun, H.H.; Seré Rabé, Carlos; Peden, Donald G. (1997)
Several studies have shown different positive and negative cases of livestock and environmental interactions in the different eco-regions of the world and under a variety of production systems. They have been related to inadequate policies, pressures for intensification of production systems led by high demands, poverty and the pressure to meet short term needs, lack of awareness about environmental consequences etc. A recent global consultation organized by ILRI, IDRC, FAO and INFORUM obtained a wide opinion of stakeholders on these issues. The consultation identified the state of the environment in different parts of the world, some of the forces that lead to the pressure on natural resources, the response of society, as well as specific reommendations for future research, and Development. Some of the challenges identified were the Development of sustainable agricultural systems for different eco-regions of the world, the need for more holistic approaches towards research and Development, and the need to formulate policy recommendations based on broad participation and knowledge. This paper identifies some of those challenges. It highlights the work of some international agencies. It explains the mechanisms utilized to get broader discussion on the main issues, the results of the consultation, and identifies opportunities for action. It identifies more specific opportunities for Canadian collaboration.